Electrospun nanofibres with pH‐responsive operational factors for controlling of chemotherapeutic drugs release performance. (22nd July 2020) - Zhang, Jing; Xu, Chengshu; Ren, Yan; Lu, Shaofeng
Abstract : In the present study, the novel keratin‐based 5‐fluorouracil (5‐FU) releasing nanofibrous system was electrospun. The pH sensitivity releasing performances of the nanofibres were optimised by a full‐factorial matrix design of experiment (DoE) with two significant factors at two levels in different pH environments. This full‐factorial DoE methods was applied to identify the main effects of these composite bio‐functional nanofibres and investigate the interaction effects of multiple factors. The SEM images indicated that a more homogeneous microstructure of the composite nanofibres was observed at the low level of electrospun voltage, which was set at 15 kV. The FTIR test detected the characteristic peaks of keratin at 1630 and 1550 cm −1 . The releasing performances were examined by ultraviolet and visible spectrophotometry. The results indicated that the ratio between keratin and poly‐L‐lactide is a major factor to control the sustained‐releasing performance. A significant pH sensitivity of the composite nanofibres was achieved after adjusting the operational factors by DoE optimisation. The drug‐loaded nanofibres with high content of keratin (50 wt%) released 48.5% of 5‐FU in pH 7.4 solution while released 83.7% of 5‐FU in pH 6.0 solution. The results indicated that these composite electrospun nanofibres can be used as a candidate of pH‐triggered biomaterials.